Ease of retrieval effects in social judgement the role of unrequested cognitions. [article]. - Tormala, Zachary L.
The present research explores a new mechanism for case of retrieval effects in social judgement. It is suggested that in the most common ease of retrieval paradigm. when it is difficult to people to generate or retrieve the specific type of cognition requested (e.g., positive thoughts about an issue or memories of assertive behavior), they are more likely to spontaneously generate of retrieve unrequested cognitions (e.g., negative thoughts about the issue or memories of unassertive behavior), and the presence of these unrequested cognitions can affect social judgement. In 4 experiments, participants were asked to generate a high (difficult) or low (easy) number of cognitions in a given direction. Across experiments, when participants were asked to generate a high number of cognitions, they also had more unrequested cognitions, and these unrequested cognitions played a mediating role in the ease of retrieval effect on judgement. in the 3rd and 4th experiments, this mechanism was found to be independent of previously identified mediators.